Preparation and Charactrisation of 1,3-dipolar cycloaddition of nitrones with 4-amino antipyrene - Dakhil Z. Mutlaq; Raad J. Ali (University of Thi-Qar Journal, 2019)
Some nitrones (1-5), derived from N–phenyl hydroxylamine with substituted benzaldehyde such as (3-chlorobenzaldehyde, 4-chlorobenzaldehyde, 3-nitrobenzaldehyde, 4-florobenzaldehyde, 2-nitrobenzaldehyde). In subsequent 1,3-dipolar cycloaddition reactions of nitrones with 4-amino antipyrene give isoxazolidines (6-10), They have been identified by 1HNMR, 13CNMR, IR and Mass spectra